2021
DOI: 10.1080/14786419.2021.1980789
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of aqueous and polyphenol-rich extracts of Larrea divaricata Cav. on a melanoma cell line

Abstract: Most of the deaths from skin cancer are caused by melanoma, a malignancy in which STAT3 plays a crucial role. The inhibition of STAT3 is considered a potential target to induce cell death, tumor regression and metastasis inhibition. The objective of this work was to evaluate the activity of the aqueous extract of Larrea divaricata (Aq), a fraction rich in polyphenols (EA),and the isolated compound quercetin-3-methyl ether (Q3ME) on B16F10 melanoma cells. The effects of Aq, EA and Q3ME were assessed on B16F10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Traditional Chinese medicine and its active molecules can inhibit the viability of tumor cells by regulating several important signal transduction pathways, including apoptosis, autophagy and polyamine metabolism [49][50][51]. Quercetin-3-methyl ether is a flavonoid widely present in traditional Chinese medicinal materials such as Bupleurum and Mulberry leaves, and is widely present in nature and daily diet [28]. Quercetin-3-methyl ether has been reported to inhibit the growth of a variety of malignancies, however, little is known about the functional effects of this compound on CRC cells and its antitumor mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional Chinese medicine and its active molecules can inhibit the viability of tumor cells by regulating several important signal transduction pathways, including apoptosis, autophagy and polyamine metabolism [49][50][51]. Quercetin-3-methyl ether is a flavonoid widely present in traditional Chinese medicinal materials such as Bupleurum and Mulberry leaves, and is widely present in nature and daily diet [28]. Quercetin-3-methyl ether has been reported to inhibit the growth of a variety of malignancies, however, little is known about the functional effects of this compound on CRC cells and its antitumor mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, many countries have utilized multiple forms of complementary and alternative medicine to combat cancer [26,27]. Quercetin-3methyl ether (Q3ME), a natural compound found in various plants, including Caesalpinia Bonduc, Larrea Divaricata Cav., Cistus Laurifolius, Polygonum amphibium [28][29][30][31], has been shown to have anti-oxidant, anti-inflammatory, anti-viral, hypoglycemic and immunomodulatory effects [32][33][34][35][36]. Most interestingly, Quercetin-3-methyl ether has obtained wide attention in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that polyphenols demonstrate anticancer properties on melanoma cell lines via their cytotoxic and anti-proliferative effects and also by participating in the regulation of cell cycle, apoptosis and autophagy [ 22 ]. Martino et al [ 23 ] suggested that the extract from Larrea divaricata Cav. could be an adjunctive therapy for melanoma due to its high content of polyphenols and their inhibitory effect on the proliferation of B6F10 cells via the inhibition of STAT3 and the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%